Learner Perceptions Regarding the Lecture and the Small Group Discussion as Teaching/Learning Methods in Physiology” (Bangladesh Journal of Medical Science, 2019)
Introduction: Physiology has traditionally been taught through lectures, but other methods are now being tried. One of these, the small group discussion (SGD), is considered to be more tuned to learners’ needs compared to the lecture.Aim: This study was undertaken to determine learner perceptions on the lecture and the SGD as teaching/learning methods in physiology.Methods: Ninety-seven first MBBS students were taught Physiology in both lecture and SGD formats for a whole year. Feedback was then obtained from the students using a validated and structured questionnaire. Data was entered in Excel sheet and analyzed using SPSS software.Results and Discussion: Learners felt that both the lecture and the SGD helped them understand basic principles well (93.4 and 93.3%), contributed effectively to the learning process (84.6 and 90%) and fostered critical thinking skills (64.9 and 68.9%). For delivery of basic concepts, learners preferred the lecture for its systematic presentation. SGDs were perceived to promote active participation of learners (85.6%), encourage facilitator-learner interaction (87.8), and retain student interest better (62.2%).Overall, learning was better-stimulated by the SGD (73.4%) rather than the lecture (35.2%).Conclusion: In the teaching/learning of physiology, appropriate use of both the lecture and the SGD will serve to nurture and sustain learner interest effectively.Bangladesh Journal of Medical Science Vol.18(2) 2019 p.274-278